The business plan of Cry Bar - Guo, Xin (2009)
Cry Bar is a Beijing-based start-up company comprising a relaxed lounge dedicated to providing comfortable and private spaces in which young people can pour out their feelings to well-trained consultants and get a good cry. It intends to gain an advantage of being the first company to target a completely new sector in China, i.e. young citizens who find themselves under pressure. It aims to become a leading provider of emotional support to local white-collar workers and college students. Market research already conducted has suggested a ready market for such a venture.